ผลของพอลิเอทิลีนชนิดความหนาแน่นปานกลาง พอลิเอทิลีนชนิดความหนาแน่นสูง และแคลเซียมคาร์บอเนตต่อสมบัติทางกายภาพของฟิล์มหดพอลิเอทิลีนชนิดความหนาแน่นต่ำ - สราวุธ แซ่โคว (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The aim of this research was to study the mechanical properties of downgauging film blends between low density polyethylene (LDPE) with high density polyethylene (HDPE), medium density polyethylene (MDPE), and calcium carbonate prepared by monolayer blown film extrusion. The compositions of LDPE/HDPE and LDPE/MDPE blends were varied from 90/10, 80/20, 70/30 and 60/40 w/w., and for LDPE/CaCO3 varied from 97.5/2.5, 95/5, 90/10 and 85/15 w/w. Film thickness of all blends was performed to very thin film at 50 micron compared to virgin LDPE film at 30, 50, 70, 90, and 110 micron. Thermal behavior, degree of crystallinity of these films and film properties of tensile strength, seal strength, shrink ability and haze were also investigated. From the results, higher content of HDPE tended to enhance the degree of crystallinity of blends due to their high linearity molecular structure and high density. On the other hand, the crystalline fraction value of LDPE/MDPE blends showed lower than that of virgin LDPE film for all compositions. However, tensile properties tended to increase when increasing all HDPE and MDPE contents but shrink ability tended to decrease. The results were also found that higher content of CaCO3 influenced to enhance tensile and shrink ability but seal strength weren’t change. These could be concluded that downgauging film of LDPE/HDPE, LDPE/MDPE blends at 70/30 w/w, and LDPE/CaCO3 at 90/10 w/w, in the thickness of 50 micron had the mechanical properties both of tensile and seal strength closed to those of virgin LDPE film having the thickness of 90 micron and 70 micron respectively. Finally, it had a possibility to reduce the amount of LDPE shrink film by downgauging method while remaining the mechanical properties of film in the range of shrink film applications.